2019
DOI: 10.1108/ihr-03-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

QSR customer sustainable behaviors and brand practice perceptions on willingness to pay a premium

Abstract: Purpose The purpose of this paper is to investigate the effect of consumer sustainability attitudes and quick service restaurants (QSRs) practices along with the willingness of consumers to pay a premium for sustainability efforts. Design/methodology/approach A random sample of QSR customers in Germany resulted in 428 completed surveys. First, common factor analysis was conducted to assess the summated scales related to the sustainable behavior of customers, the importance attached by them to the different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Moreover, in order to attract more tourist service providers must provide quality goods and services in a clean and hygienic environment. Further, Ottenbacher et al (2019) suggested that sustainability efforts are primarily driven by internal beliefs as well as behaviours of customers themselves rather than by the mere actions of firms. This means that customer education is necessary for achieving sustainable tourism goals.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Moreover, in order to attract more tourist service providers must provide quality goods and services in a clean and hygienic environment. Further, Ottenbacher et al (2019) suggested that sustainability efforts are primarily driven by internal beliefs as well as behaviours of customers themselves rather than by the mere actions of firms. This means that customer education is necessary for achieving sustainable tourism goals.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…From the point of view of academic contributions, the present study includes the increasing research on the relationship between the consumer and the QSRs (e.g. Ottenbacher et al, 2019;Su, 2011;Ottenbacher and Harrington, 2009) by empirically addressing the relationships between innovative practices (IP), customer experience (CE), customer satisfaction (CS) and customer loyalty in select QSRs. The findings of this study have significant implications for the hospitality industry, as the implementation of innovative practices has a significant impact on Quick Service Restaurants.…”
Section: Theoretical Implicationmentioning
confidence: 99%
“…FFRs that engage in sustainable practices have a competitive advantage over competitors (Tien & Hung Anh, 2018). Many FFRs have become greener as a result of implementing social and environmentally sustainable practices (Ottenbacher et al, 2019). Sustainability, as well as the use of locally grown and sourced meats and produce, have emerged as major trends in the restaurant industry (National Restaurant Association, 2020).…”
Section: Sustainability Consumers and Fast-food Industrymentioning
confidence: 99%